Piezoelectric Materials and Devices Practice and Applications - Ebrahimi, Farzad (IntechOpen, 2013)
This book is a result of contributions of experts from international scientific community working in different aspects of piezoelectric materials and devices through original and innovative research studies. Through its 7 chapters the reader will have access to works related to the various applications of piezoelectric materials such as piezoelectric stacks in level sensors, pressure sensors, actuators for functionally graded plates, active and passive health monitoring systems, machining processes, nondestructive testing of aeronautical structures and acoustic wave velocity measurements. The text is addressed not only to researchers, but also to professional engineers, students and other experts in a variety of disciplines, both academic and industrial seeking to gain a better understanding of what has been done in the field recently, and what kind of open problems are in this area.